Spatial suitability evaluation and layout optimization of emergency shelter: A case study in Tianhe District of Guangzhou City - Bo Tang; Zongyuan Li; Yinzhong Chen (Heliyon)
Emergency shelters are multifunctional spaces that provide safe refuge, essential life protection, and rescue command for residents in case of urban disaster. These shelters constitute crucial components of urban public safety. This study, with Tianhe District in Guangzhou City as a case study, used data from emergency evacuation sites and other socio-economic sources to construct an evaluation system for spatial suitability evaluation and layout optimization of emergency shelters. This paper utilized from GIS-based methods including Grey Correlation Method (GCM) and Entropy Weight Method (EWM), the research process of “suitability evaluation —evacuation gap analysis—site selection—site optimization”is established, and the suitability evaluation results are calculated from the combination of effectiveness, accessibility and safety; based on the principles of fairness, accessibility, safety and feasibility, combined with the analysis of the current situation of land use and evacuation demand, the layout of urban emergency evacuation sites is adjusted. Finally, the spatial layout optimization plan for emergency shelters in Tianhe District was obtained. The results show that: (1) the overall suitability of the 50 emergency shelters in Tianhe District is favorable: 21 shelters are classified as “suitable,” 25 shelters as “slightly suitable,” and four as “unsuitable.” (2) Most significant evacuation gaps are located in the peripheral areas of Tianhe District. By adding five new evacuation sites to optimize the existing layout, the evacuation coverage increased from 68.4 % to 85.2 %. Consequently, the number of people in need of evacuation decreased from 387,900 to 80,100, so the reasonable allocation of evacuation space has been significantly improved. At the same time, the optimised scheme increases the density of emergency shelters and reduces the overlap of services to some extent. Evaluating the appropriateness and optimizing the spatial layout of urban emergency shelters can enhance disaster prevention and response capacity in megacities. This approach is of great practical value for the construction of resilient cities and the implementation of sustainable development strategies.